T-Shaped MIMO Antenna Design with Defected Ground Structure and Parasitic Elements for 5G Application - Sherila, Ayu Mika; Umaisaroh, Umaisaroh; Alaydrus, Mudrik (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2025)
5G technology is designed to improve efficiency, network capacity, data rate, and coverage with low power consumption. This requires the design of suitable antennas for 5G wireless communications to achieve optimal bandwidth, radiation, efficiency, and performance. MIMO antenna designs use multiple antennas and face the main challenge of reducing mutual coupling between adjacent antenna elements. In this study, the MIMO antenna is designed using T-shaped DGS Technique and parasitic elements. The DGS technique is developed by creating a specific area on the ground plane of the antenna to improve its performance. By incorporating DGS concepts and parasitic elements into the design, the aim is to achieve large bandwidth and high gain. This antenna has dimensions of 52 mm x 12 mm and is simulated using Ansys HFSS software. Measurement results for the antenna using Rogers Duroid RT5880 substrate show a mutual coupling value of -54.2 dB, return loss of -11.1 dB, gain of 13.11 dB, and a sufficiently wide bandwidth. Thus, the proposed antenna can operate at a frequency of 28 GHz, meeting the requirements for 5G applications.